A construção social do campo da arquitetura moderna em Belo Horizonte - Juliano Nemer Caldeira Brant (2012)
This work approaches the history of the modern architectural field constitution in Belo Horizonte, seeking to evidence that it happened because of an ample social project, with roots even before the construction of the city, in the academic, cultural and social formation of its idealist. For the elaboration of the dissertation, a bibliographic and documental research was carried out, looking for relevant data in order to understand this process. The reflections on the historical data have support on the concepts and theories of the French sociologist Pierre Bourdieu- particularly habitus, field and capital and symbolic power and in the interpretation of those concepts and theories directed to the architectural field by the architect and sociologist Garry Stevens. The approach comprise the period between the beginning of the citys foundation until the creation of the School of Architecture of Minas Gerais, in the decade of 1930 and the consolidation of the modern architecture field in that school. In order to do so, initially the civil construction field was analyzed in the first years of the capital, the ideology a actuation of the modernist intellectuals in Belo Horizonte during this period, as well as their connection with the vanguard of the Paulista (from the state of São Paulo) Modernism. Discussing then the participation of Mineiros (from the State of Minas Gerais) intellectuals in the Ministry of Education and Health lead by Gustavo Capanema in the New State. The dispute over the conception of that institutions building, that came to be the architectural landmark of the Brazilians modernism, is understood as competition for symbolic capital,particularly considering the actions of the French-Swiss architect Le Corbusier in this context and his relationship with modernist Brazilian architects. Finally, the history of the architectural modernism consolidation in Belo Horizonte is approached from the foundation of the School of Architecture, going through the production of this school in the early decades, until the work of architect mineiro (from the State of Minas Gerais) Sylvio de Vasconcellos and his engagement in the modernism legitimization, which can be seen in texts published in the newspaper Estado de Minas and assembled in the book Notions of Architecture, 1962.